Optimizing Sustainability through 7P Marketing Mix at MCA House in the Development of Halal Modest Fashion Industry - Izniyah, Izniyah; Rahmawati, Lilik; Mazza Basya, Maziyah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The halal modest fashion industry has seen a marked increase in recent years. In this situation, MCA House, a company engaged in modest fashion, has played an important role in the development of this industry. The purpose of this journal is to analyze and evaluate the marketing strategy of 7P mit (Product, Price, Place, Promotion, People, Process, Physical Evidence) applied by MCA House in the development of halal modest fashion industry. The research method used is descriptive qualitative research. Data were collected through in-depth interviews with the marketing manager of MCA House and direct observation of the company's operations. The analysis shows that MCA House has a solid and comprehensive marketing strategy that implements the 7P mix effectively In the product aspect, MCA House offers a variety of modest clothing with trendy designs and in accordance with halal principles Pricing is done by considering quality factors, market purchasing power, and product excellence. In terms of distribution, MCA House uses online and offline distribution channels to ensure product accessibility Promotion is done through social media campaigns, collaboration with influencers, and participation in fashion events. In addmon, MCA House also prioritizes customer experience and provides quality services An easy and efficient purchasing process, as well as friendly and knowledgrable staff, provades high customer satisfaction. The physical evidence presented through attractive product packaging and aesthetically pleasing store presentation also provades a positive customer experience. In conclusion, the 7P marketing mix strategy implemented by MCA House helps in the development of the halal modest fashion industry